Direct Calculation of the Variance of Maximum Penalized Likelihood Estimates via EM Algorithm. - Lee, Woojoo; Pawitan, Yudi (American Statistician, 2014)
The variance of the maximum penalized likelihood estimate obtained through the EM algorithm has not been explored in detail. We provide a simple and intuitive new representation for the variance that can be computed from the EM algorithm directly. For pedagogical purposes, we illustrate the new formula with two examples where analytical solutions are possible.